Factors Affecting The Policy of Labor Placement in Cirebon City - Hery Nariyah; Soleh Suryadi; Thomas Bustomi; Denok Sunarsi (Doctoral Program of Social Science Pasundan University, 2021)
This research aimed to analyze and find out the extend to which the implementation of the employment placement policy performed by Regional Office of Manpower of Cirebon City and find out the factors affecting the employment placement policy effectively; This research used qualitative descriptive method in which the data sources in this research were obtained through direct observation by the researcher and guided interview with the implementing officers or apparatus carrying out the policy in Regional Office of Manpower of Cirebon City. The findings showed that the implementation of the employment placement policy in Cirebon City had not performed effectively. The factors which needed to be considered in the employment placement were: (1) Education: Public had not had the competence and the education quality was still in low level, (2) Occupational knowledge; Labors must still complete a series of Academic Achievement tests, (3) Occupational skill; Labors were still not ready with the skills needed by companies, (4) Work experience; Labors still needed to be given the Orientation Program and Human Resources Development Program by Regional Office of Manpower. The factors affecting the implementation of the employment placement policy; from the five theoretical concepts of Rondonelli and Chabeer Cheema’s opinion used in analyzing this research, they could also be seen that they could test the implementation of the employment placement policy, namely: (1) Environmental conditions that public had not completely had adequate skills, (2) Employment relationship among organizations; Good coordination was needed between Regional Office of Manpower and D.KISS related to valid data regarding the number of labors, (3) Availability of Resources; Funds available in APBD of Cirebon City for Regional Office of Manpower had not reflected the existence of budget leading to specific activities for the employment placement, (4) Characteristics of implementing agencies; It had not depicted the overall activities of Regional Office of Manpower especially the job introductory officer and labor distributor were not clear organizationally, (5) Performance and impact; Regional Office of Manpower had not fully had the authority in the employment placement, only limited to recommending labors with various dimensions. It turned out that the result was that Regional Office of Manpower of Cirebon City had not been effective in its implementations, so it affected the minimum or only few labors who had registered with labor users in companies or agencies that needed them. Based on the results of the discussion that had been stated, it could be said that the novelty of this research was it could found the weaknesses of Rondonelli and Chabeer Cheema’s theory used to analyze the implementation of the policy, namely: (1) Clarity of Regulation; there had been no Regional Regulation regulating Manpower, (2) Local wisdom, it had not considered the local culture, (3) Strategy; there had been no strategy, so it needed to be combined with a SWOT analysis formulating a strategy by considering strengths, weaknesses, threats, and opportunities.